Effects of pesticides on the soil microbial biomass and microbial activity - Hart, Murray (1995)
This thesis describes research investigating the side-effects of pesticides on soil microbial biomass and microbial activity, with particular reference to two recently developed pesticides, a fungicide, epoxiconazole, and a herbicide, quinmerac. In a dose-responsee xperiment,a pplication of thesep esticidest o a sandy loam soil, at up to 10 and 20 times field rate, had no significant effect on soil microbial biomass C or ninhydrin-reactive N, over 84 days incubation. There was also no effect on soil respiration, except for the higher rate quinmerac-treated soil, which evolved 13% lessC02-Cthan the control. The rate of mineralisation of epoxiconazole and quinmerac, and their long-term effect on soil respiration, were measured in three contrasting soils: a sandy loam, a silty clay loam, and a clay soil, using 14C -labelled active ingredients. The kinetics of the pesticides' mineralisation were quite different, epoxiconazole being hyperbolic, while quinmerac was sigmoidal. The maximum amount of mineralisation of both pesticides occurred in the silty clay loam soil, which had the lowest microbial biomass content. The mineralisation of the pesticides was increased by the addition of ryegrass, with the greatest effect in the silty clay loam soil, probably because of the large ryegrass C: biomass C ratio. The mineralisation of epoxiconazole was affected by the ryegrass amendment much more than quinmerac. Further additions of the pesticides had no significant effect on soil respiration or pesticide mineralisation. The mineralisation of epoxiconazole and quimnerac was further investigated in the silty clay loam soil, using samples with different crop management histories, and the effects of ryegrass and glucose amendment. Pesticide mineralisation was shown to be related to the amount of soil microbial biomass, indicating that the difference in mineralisation rate between the three soil types above was not due to differences in their crop management, but innate differences in soil chemistry and microbiology. Ryegrass addition stimulated the mineralisation of epoxiconazole more than quinmerac, while the reverse was true for glucose, indicating that the pesticides were being degraded by two distinct fractions of the microbial biomass. The effects of long-term cumulative field application of the pesticides benomyl, chlorfenvinphos, aldicarb, triadimefon and glyphosate, on soil microbial biomass and mineralisation of soil organic matter were investigated. The addition of aldicarb consistently increased the microbial biomass, due to its beneficial effect on crop growth, but this effect was not reflected in the rate of organic matter mineralisation. However, in general, the continued application of these pesticides for up to 19 years, at slightly higher than the recommended rates, had very little effect on the soil microbial population. The effects of epoxiconazole and triadimefon on soil ergosterol content and microbial biomass C were compared in a sandy loam soil. Both pesticides temporarily reduced soil ergosterol by about 30%, while biomass C remained largely unaffected. However, when straw was added to the soils, the inhibition of ergosterol was still evident, as was an inhibitory effect on biomass C. The measurement of soil ergosterol was more sensitive to the pesticide effects than biomass C, and could be a useful test in determining changes in fungal populations.